ANALYSIS OF THE INTRAOPERATIVE ULTRASOUND RESULTS IN THE SURGICAL TREATMENT OF RENAL TUMORS - A. D. Karnin; A. A. Kostin; S. O. Stepanov; N. V. Vorobyev; P. D. Bespalov; V. O. Dimitrov (Исследования и практика в медицине)
Purpose. To evaluate the effectiveness of intraoperative ultrasonography (IOUS) in the surgical treatment of kidney tumors.Patients and methods. Possibilities of IOUS application in the surgical treatment of kidney tumor according to the results of examination and surgical treatment of 145 patients (95 men and 50 women) diagnosed with kidney cancer were evaluated. The patients were divided into 2 groups: group 1 (comparisons) — 76 patients; during the examination and treatment, the IOUS method was not used, group 2 (basic) — 69 patients, who during the surgical treatment used the IOUS method to further clarify the localization, the size and boundaries of the tumor formation.Results. The use of IOUS helped to reduce the frequency of nephrectomy (11.9% in the comparison group and 8.7% in the main group), and reduce the frequency of intraoperative complications, which amounted to (8.7% against 13.2%). The frequency of damage to the spleen and the transition to open surgery did not differ. The use of IOUS allowed to characterize in detail the anatomical features of the tumor, its vascularization and to implement the RENAL prognosis: favorable — in 50.7% of patients, unfavorable — in 15.9%.Conclusion.When performing kidney tumor surgery, it is recommended to perform IOUS of the affected kidney in order to further clarify the boundaries of the tumor lesion to improve the effectiveness of the operation.